2017
DOI: 10.5009/gnl15424
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Tunnel Dissection for Upper Gastrointestinal Submucosal Tumors Originating from the Muscularis Propria Layer: A Single-Center Study

Abstract: Background/AimsIn recent years, endoscopic submucosal tunnel dissection (ESTD) has gained popularity worldwide. The aim of this study was to evaluate the safety and efficacy of ESTD in treating upper gastrointestinal submucosal tumors (SMTs) in a large-volume endoscopic center.MethodsPatients with SMTs were enrolled in this study between January 2012 and January 2015. Demographic data, clinical data, and treatment outcome were collected and analyzed.ResultsSeventy SMTs originating from the muscularis propria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…While maintaining mucosal integrity, STER seems preferable to pure EFTR for lesions located in areas of the GI tract where tunneling is feasible . STER can resect SMT under direct vision and, consequently, the risk of gastrointestinal tract infection and leakage is theoretically reduced, yielding good clinical results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While maintaining mucosal integrity, STER seems preferable to pure EFTR for lesions located in areas of the GI tract where tunneling is feasible . STER can resect SMT under direct vision and, consequently, the risk of gastrointestinal tract infection and leakage is theoretically reduced, yielding good clinical results …”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] STER can resect SMT under direct vision and, consequently, the risk of gastrointestinal tract infection and leakage is theoretically reduced, yielding good clinical results. 48 A comparative study between STER and the thoracoscopic enucleation approach concerning large symptomatic esophageal SMT was recently published reporting shorter procedure time and hospital stay in the STER group. 49 Gastric and duodenal SMT National Comprehensive Cancer Network (NCCN) guidelines recommend surgery for suspected GIST 2 cm or larger and endoscopic surveillance of those smaller than 2 cm, but the ESMO group proposed resection for all histologically diagnosed small GIST.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to esophageal neoplastic lesions, ESTD can also be used to resect submucosal tumors originating from the muscularis propria layer of the upper digestive tract. Many recent studies have reported the efficacy and safety of ESTD for resection of tumors from the upper gastrointestinal submucosal [33][34][35]. In 2014, Hayashi et al first reported the use of ESTD for colorectal lateral spreading tumors and named this technique the "pocket-creation method" [36].…”
Section: Discussionmentioning
confidence: 99%
“…After searching lesions originating from the muscularis propria on PubMed [ 1 , 2 , 11 , 15 20 ], we have found a total of 532 report cases; among them, 76.69% (408/532) were leiomyomas, 22.18% (118/532) were stromal tumors, and 0.56% (3/532) were lipomas, while there was only 1 case of granular cell tumor, calcifying fibroma, schwannoma, and cystic lesion, respectively. Thus, we concluded that CLMPGC is a very rare and a benign disease.…”
Section: Discussionmentioning
confidence: 99%
“…The gastric cardia is the most common site of gastric submucosal tumors [ 1 ], most of which are leiomyomas and stromal tumors. Cystic lesions originating from the muscularis propria of the gastric cardia (CLMPGC) are considered a rare benign disease [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%